Excess Thermodynamic Properties and Ftir Spectroscopy of Aceton-Isopropanol Liquid Binary Mixture (Journal of University of Babylon for Engineering Sciences, 2018)
Experimental investigation was done using different instruments for the testing the properties of density, surface tension and viscosity in the case of pure and mixture system at the normal temperature of 25 oC and 1 atm. Excess volume was found to exhibit negative value at a mole fraction of 0.5. The deviation in the surface tension and viscosity were found of a positive value at the mole fraction value of 0.5. The experimental excess properties were correlated using the Redlich-Kister (RK) equation and showed an accepted standard deviation. The intermolecular interaction between acetone and isopropanol was found of negligible effect and showed a weakness in the hydrogen bonding according to the FTIR spectra for the mixture of acetone and isopropanol which agreed with the positive values of excess molar volume. Moreover, the values of surface tension and viscosity deviations were found of negative values for all the mole fraction range studied.